Universal accounts at birth: building knowledge to inform policy - Sherraden, Michael; Clancy, Margaret; Nam, Yunju; Huang, Jin; Kim, Youngmi; Beverly, Sondra; Mason, Lisa; Wikoff, Nora; Schreiner, Mark; Purnell, Jason (University of Chicago Press, 2015)
Objective: This article summarizes the design, implementation, and early findings of a statewide randomized experiment of Child Development Accounts (CDAs). The SEED for Oklahoma Kids experiment (SEED OK) is testing a concept for a universal, progressive asset-building policy with potential for national application. CDAs can start as early as birth, providing structured opportunities (e.g., financial access, information, incentives) to encourage asset accumulation for postsecondary education and other developmental purposes. Theory and evidence suggest that CDAs can improve educational outcomes, especially among disadvantaged youth. Method: Participating in a rigorous randomized controlled design, primary caregivers of children born in Oklahoma in 2007 completed a baseline telephone survey before random assignment to the treatment group (n = 1,358) or control group (n = 1,346); these caregivers completed a followup survey 4 years later. For children in the treatment group, the SEED OK experiment automatically opened an Oklahoma 529 College Savings Plan (OK 529) account with a $1,000 initial deposit. In addition, low- and moderate-income families in the treatment group were eligible for a savings match for deposits to their own OK 529 accounts. Results: Findings indicate that CDAs can be implemented universally in a full population to increase the accumulation of college assets. The CDA in SEED OK greatly reduces disparities in OK 529 asset accumulation associated with socioeconomic characteristics. The CDA also has positive effects on parental educational expectations for children, maternal depressive symptoms, and children’s social-emotional development. Conclusions: In contrast to college savings programs that require parents to open an account, SEED OK’s universal, automatic, and progressive CDA model gives all children the opportunity to benefit from college account and asset ownership.